Comparative Study of Multibit LSB Steganography with Cryptography - Mandeep Kaur, Gill; Rupinder Kaur, Randhawa (International Journal of Computer Sciences and Engineering, 2025)
Security has an important role in data communication through internet. When data travel through public network, sometimes unaccredited users access the confidential data. For secure communication various techniques are used from ancient time to the present time. Steganography is such type of technique used for data transmitting through insecure network. It is an art of hiding information inside other cover media such as text, image, audio and video. Various types of Steganography techniques are Text Steganography, Image Steganography, Audio and Video Steganography. But from these, Image Steganography is more usable due to increased frequency of images on the internet. Cryptography is a technique used for encrypting the plain text into cipher text securing from hackers. Cryptography is disparate from Steganography. In Cryptography, data is converted into different form of data. But in Steganography, data are invisible inside other data. In Cryptography, third party knows the presence of the secret message. In Steganography, unauthorized users do not know about the presence of the secret message. Hence, amalgamation of Steganography and Cryptography gives meticulous results. This paper instigates comparative study of pure LSB Steganography and LSB Steganography with Cryptography. One bit and two bits LSB steganography is implemented. Data are encrypted using RSA algorithm. Proposed technique is used to compare results of MSE (mean square error), RMSE (root mean square error), PSNR (peak signal to noise ratio) and NC (normalized coefficient) for both techniques.